(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cybercrime is a rapidly growing problem in India, with a significant impact on women. This study aims to critically examine the nature and extent of cybercrimes committed against women in India, with a focus on the legal framework and enforcement mechanisms in place to address these crimes.